1986
DOI: 10.1136/adc.61.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mechanism of bradycardia during apnoea in preterm infants.

Abstract: SUMMARY Bradycardia occurred during 363 of 1520 apnoeas of 10 seconds' duration recorded in 28 preterm infants. The incidence increased with increasing duration of apnoea (10% of 10-14 seconds, 34% of 15-20 seconds, and 75%/O of >20 seconds, p<0-001). This was similar for each type of apnoea-central, mixed, and obstructive. During 133 apnoeas in five infants the time from the start of the apnoea to the onset in the fall in oxygen saturation (mean 6-9 seconds) was significantly related to the onset of the fall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…[31][32][33] The heart must not slow excessively, however, otherwise dangerous circulatory depression could ensue. For this reason, vagal potentiation is considered a likely lethal predisposing factor in sudden infant death syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] The heart must not slow excessively, however, otherwise dangerous circulatory depression could ensue. For this reason, vagal potentiation is considered a likely lethal predisposing factor in sudden infant death syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism of development of bradycardia has been subject of debate among various investigators. [56][57][58] Carbone et al 59 reported that apnea and drop in heart rate began simultaneously in 14% of medium and 25% of short apneas. Simultaneous development of apnea and bradycardia can be attributed to enhanced inhibitory responses to airway afferent stimulation.…”
Section: Relationship To Bradycardiamentioning
confidence: 99%
“…These studies did not measure oxygenation continuously, so both hypotheses remained essentially speculative. In 1986, HendersonSmart et al (8) recorded Sao2 during episodes of apnea and bradycardia in five preterm infants, using an ear oximeter with an electronic response time of 0.1 s. They reported that the interval between the onset of apnea and the onset of the fall in Sao2 was shorter than that between the onset of apnea and the onset of bradycardia and concluded that the bradycardias occurred as a response to a fall in Sao2. This conclusion, however, was recently challenged by Upton et al (9), who warned, appropriately, against infemng a cause-and-effect relationship from observations on the temporal relationship between hypoxemia and bradycardia.…”
mentioning
confidence: 99%